MODEL DINAMIS AUTOREGRESSIVE DISTRIBUTED LAG (STUDI KASUS: PENGARUH KURS DOLAR AMERIKA DAN INFLASI TERHADAP HARGA SAHAM TAHUN 2014-2018) - AQIBAH, MAHMUDATUL; SUCIPTAWATI, NI LUH PUTU; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 9 No 4 (2020)DO - 10.24843/MTK.2020.v09.i04.p304, 2020)
The aim of this research is to determine the dynamic model equation of autoregressive distributed lag by using koyck method, to find out the effect of log US dollar exchange rate and log inflation on log stock price in 2014 2018, and to forecast value of log stock price on January 2019 August 2019. The data used in 2014 2018. The data was transformed into logarithm format. T ime series plot of log US dollar exchange rate, log inflation, and log stock price suggest that the fluctuation in the data, for instance, both upward and downward trends, during the period. We obtained that the Koyck transformation could changed the lag distribution model into autoregressive distributed lag (ARDL) dynamic model. Furthermore, the log of US dollar exchange rate and log inflation have negative effect on log stock price in particular period. We measured forecasting accuracy using mean absolute prediction error (MAPE) and concluded that ARDL forecasting using Koyck model shows a significant increase in stock price.